1997
DOI: 10.1023/a:1018683823020
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A unique property of smooth muscle is its ability to maintain force with a very low expenditure of energy. This characteristic is highly expressed in molluscan smooth muscles, such as the anterior byssus retractor muscle (ABRM) of Mytilus edulis, during a contractile state called 'catch'. Catch occurs following the initial activation of the muscle, and is characterized by prolonged force maintenance in the face of a low [Ca2+]i, high instantaneous stiffness, a very slow cross-bridge cycling rate, and low ATP u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…We have shown that the catch state is regulated by the cAMP-dependent phosphorylation of a high molecular mass (Ϸ600 kDa) protein in the intact and permeabilized ABRM (15). Several lines of evidence support this conclusion.…”
mentioning
confidence: 56%
“…We have shown that the catch state is regulated by the cAMP-dependent phosphorylation of a high molecular mass (Ϸ600 kDa) protein in the intact and permeabilized ABRM (15). Several lines of evidence support this conclusion.…”
mentioning
confidence: 56%
“…The supernatant and pellet were applied to SDS-PAGE. The in vivo molar ratio of twitchin/ myosin is 1:15 (6), and the higher levels of TWD2-S were used to facilitate its detection on gels.…”
Section: Methodsmentioning
confidence: 99%
“…Twitchin phosphorylation is required for relaxation of the muscle from catch. For this cycle to repeat, dephosphorylation of twitchin is necessary (6). Thus, in this scheme, twitchin is a major regulator of the catch state.…”
mentioning
confidence: 99%
“…Of course, force maintenance by these tethers does not require any energy input. Given that there is one twitchin for every 15 myosin molecules (9), there would be a twitchin-mediated link between filaments for every 7-8 myosin cross-bridges. Importantly, phosphorylation causes a decrease in binding of both links, allowing rapid relaxation of catch force and loss of resistance to lengthening.…”
Section: Discussionmentioning
confidence: 99%
“…The protein that is phosphorylated by PKA during relaxation of catch force is twitchin, and it is the phosphorylation state of this protein that determines the presence or absence of the catch state at basal [Ca 2ϩ ] (9,10). Twitchin is so named because Caenorhabditis elegans mutants that lack the protein show nearly constant twitching of body wall muscles (11).…”
mentioning
confidence: 99%